2020
DOI: 10.1002/tie.22186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on use of wasta among human resources management practitioners

Abstract: The practice of wasta dominates all aspects of Arabs' lives; it is a parallel inegalitarian system that categorizes people according to their connections. One of the epicenters of wasta is human resources management (HRM). This article studies the concept of wasta in the Arab world by examining its use in HRM according to gender, in the case of the Jordanian public sector. Results obtained from 27 semi‐structured interviews of HR managers indicate that though wasta is an important feature of HRM in general, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 90 publications
2
32
0
Order By: Relevance
“…We followed the method by Gioia et al ( 2013 ) and Gioia et al ( 2022 ) to analyze the qualitative data. The method emphasizes a carefully determined data structure and theoretical abstraction based on the interviewees’ responses, and it has been used in a number of studies (e.g., Alsarhan et al, 2021 ; Spieth et al, 2019 ; Suseno & Abbott, 2021 ). It allows for a close link between what interviewees say and the abstract themes as part of the analysis (Gioia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We followed the method by Gioia et al ( 2013 ) and Gioia et al ( 2022 ) to analyze the qualitative data. The method emphasizes a carefully determined data structure and theoretical abstraction based on the interviewees’ responses, and it has been used in a number of studies (e.g., Alsarhan et al, 2021 ; Spieth et al, 2019 ; Suseno & Abbott, 2021 ). It allows for a close link between what interviewees say and the abstract themes as part of the analysis (Gioia et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its rapid economic growth, Korea remains a patriarchal society with gendered family roles based on Confucian familism (Lee, 2018 ; Lee et al, 2016 ; Tung et al, 2013 ). Research has found that the entrenched patriarchal structures, favoring men and excluding women from being hired and promoted, can lead to negative economic effects (Alsarhan et al, 2021 ; Kim, 2008 ). Gender-balanced economies, on the other hand, fare significantly better in terms of their economic performance (Council on Foreign Relations, 2021 ; OECD, 2014 ).…”
Section: The Contextmentioning
confidence: 99%
See 3 more Smart Citations